PENERAPAN METODE PEMBELAJARAN DEMONSTRASI UNTUK MENINGKATKAN PEMAHAMAN TENTANG TATA CARA SHOLAT FARDHU PADA SISWA KELAS V SD NEGERI 095147 PONDOK ATAS - Lasini Lasini (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This classroom action research was carried out in 2 cycles, each cycle carried out using a demonstration learning method by continuously realizing a learning process oriented to student activities and ultimately improving student learning outcomes. This research was conducted in class V SD NEGERI 095147 PONDOK ABOVE, totaling 13 people. After this research lasted for two cycles, the following results were obtained: 1) Student learning activities were getting better in cycle II when compared to cycle I. In cycle I, writing and reading activities decreased from 53.81% to 19.63%. doing LKS from 29.05% to 19.63%, asking friends from 12.86% to 19.63%, asking the teacher from 12.38% to 8.89%, irrelevant activities from 15.71% to 5.56%. This proves that student learning activities are getting better in cycle II when compared to cycle I. 2) Student learning outcomes are getting better when compared to the initial data, cycle 1 and cycle 2. Where in the initial data the highest score is 70, cycle I is 80, Cycle I II 100, the lowest value of initial data 50, cycle I 60, cycle II 70, the average initial data 61.54, cycle I 71.54, cycle II 86.92, classical completeness of initial data 0%, cycle I 76.92 %, cycle II 100%. This proves that student learning outcomes in PAI subjects in class V SD NEGERI 095147 PONDOK ATAS 2018/2019 academic year are increasing by using demonstration learning methods on the material for fardhu prayers.